A Novel STAT3 Mutation in a Qatari Patient With Hyper-IgE Syndrome - Chaimowitz, Natalia S.; Branch, Justin; Reyes, Anaid; Vargas-Hernández, Alexander; Orange, Jordan S.; Forbes, Lisa R.; Ehlayel, Mohammed; Purayil, Saleema C.; Al-Nesf, Maryam Ali; Vogel, Tiphanie P. (Frontiers in Pediatrics, 2019)
Autosomal dominant hyper-IgE syndrome caused by mutations in the transcription factor STAT3 (AD-HIES) is characterized by a collection of immunologic and non-immune features including eczema, recurrent infections, elevated IgE levels and connective tissue anomalies. We report the case of a Qatari child with a history of recurrent staphylococcal skin infections since infancy, who was found to have a novel, de novo mutation in STAT3 (c.1934T>A, p.L645Q). The absence of mucocutaneous candidiasis and undetectable IgE levels until the age of 7 years prolonged the time to molecular confirmation of the cause for the patient’s immune deficiency. STAT3 p.L645Q was found to have decreased transcriptional capacity. The patient also had low levels of Th17 cells and STAT3 phosphorylation was impaired in patient-derived cells. Nearly 100 unique mutations in STAT3 have been reported in association with AD-HIES.